Evolutionary aspects of immunoglobulin heavy chain variable region (VH) gene subgroups. - Rechavi, G (1983)
We isolated and determined the sequences of two human germ-line heavy chain variable region (VH) genes and compared them with mouse VH genes. The results show that the human VHI subgroup is evolutionarily related to the mouse VHII subgroup. Evolutionary preservation of homologies in VH genes of the same subgroup includes not only the coding region but also intron size and homology in noncoding regions. This suggests that a VH gene subgroup constitutes a multigene family that undergoes concerted evolution. The homology between genes of the same subgroup in different species is greater than that between genes of different subgroups within a species. One of the VHII genes contains, in complementarity-determining region 2 (CDR2), a 13-base-pair previously shown to be in CDR2 of a VHIII gene and in a heavy chain diversity region gene, DH [Wu, T. T. & Kabat, E. A. (1982) Proc. Natl. Acad. Sci. USA 79, 5031-5032], suggesting the insertion of diversity region gene sequences into the VH gene. One of the human VH genes is a pseudogene because of a terminator, which, together with our previous results, shows that the VH gene repertoire contains 40% pseudogenes. In one of the VH genes, direct and inverted repeats at both 5' and 3' ends of the gene suggest a potential transposable element that encompasses the entire VH gene. It is possible that such a structure may facilitate saltatory replication and rapid expansion of VH gene families.